Increasing dominant follicular proportion negatively associated with good clinical outcomes in normal ovarian responders using the depot GnRH agonist protocol: a large-sample retrospective analysis - Houming Su; Youhua Lai; Jie Li; Tingting Liao; Licheng Ji; Xinyao Hu; Kun Qian (BMC, 2022)
Abstract Background Currently, there is no universal criteria for the trigger time of controlled ovarian hyperstimulation (COH), especially with the emerging depot GnRH agonist protocol. It is challenging to explore an indicator that is representative of target follicle cohort development as an alternative to the conventional approach of determining the trigger time based on a few leading follicles. Methods This was a large-sample retrospective analysis. Between January 2016 and January 2020, 1,925 young normal ovarian responders who underwent their first in vitro fertilisation (IVF)/intracytoplasmic sperm injection (ICSI) cycle using the depot GnRH agonist protocol were included. They were divided into three groups based on the dominant follicular proportion (DFP, defined as the ratio of ≥ 18 mm dominant follicles/ ≥ 14 mm large follicles on the human chorionic gonadotropin (HCG) day; Group A: < 30%; Group B: 30%−60%; and Group C: ≥ 60%). The binary logistic regression and multivariate linear regression were used to assess whether the DFP was associated with clinical pregnancy, the number of frozen blastocysts, the blastocyst formation rate, and the low number of frozen blastocysts. Results The logistic regression analysis showed that compared with Group A, the odds ratio (OR) for clinical pregnancy was 1.345 in Group B (P = 0.023), and there was no statistical difference between Group C and Group A (P = 0.216). The multivariate linear regression analysis showed that DFP was negatively associated with the number of frozen blastocysts (β ± SE: Group B vs. Group A = − 0.319 ± 0.115, P = 0.006; Group C vs. Group A = − 0.432 ± 0.154, P = 0.005) as well as the blastocyst formation rate (β ± SE: Group B vs. Group A = − 0.035 ± 0.016, P = 0.031; Group C vs. Group A = − 0.039 ± 0.021, P = 0.067). Furthermore, the OR for the low number of frozen blastocysts was 1.312 in Group B (P = 0.039) and 1.417 in Group C (P = 0.041) compared to Group A. Conclusions For young normal ovarian responders using the depot GnRH agonist protocol, increasing DFP might reduce the developmental potential of oocytes and reduce the number of available blastocysts, and this might result in a lower cumulative pregnancy rate. However, further confirmation using strict prospective randomised controlled studies is required.